Elizabeti's doll - Stuve-Bodeen, Stephanie, 1965-; Hale, Christy (New York : Lee & Low Books, 1998)
When a young Tanzanian girl gets a new baby brother, she finds a rock, which she names Eva, and makes it her baby doll.
4.6
K-3
K-3
Wilson's Children
Elem. School Library Collection
School Library Journal starred
Keywords: Dolls -- Fiction; Rocks -- Fiction; Dolls -- Fiction; Rocks -- Fiction; Tanzania -- Fiction; Tanzania -- Fiction